solution-1759325
solution-1759325
solution-1759325
REVISION TEST 6
Class 12 - Mathematics
Section A
1. (a)
Det (A)
Explanation:
|B-1AB| = |B-1| × |A| × |B|
1
× |A| × |B| = |A|
B
2. (a) 9
Explanation:
IAA'| = |A| |A'| = (-3)(-3) = 9
3. (a) 16
Explanation:
Since, A is a square matrix of order 3 i.e. n = 3
we know that
|adj A| = (A)n-1
2
=2 (3−1)
...(∵ |A| = 2)
= 24
= 16
d −b
4. (a) [ ]
−c a
Explanation:
a b
S = [ ]
c d
M11 = d ⇒ A11 = d
M12 =c ⇒ A12 = -c
M21 =b ⇒ A21 = -b
M22 =a ⇒ A22 = a
d −b
⇒Ad(A) = [ ]
−c a
5.
(c) ±2
Explanation:
Since, the area of the △ABD is 3 sq units, then we have
∣1 3 1∣
1 ∣ ∣
0 0 1 = ±3
2 ∣ ∣
∣k 0 1∣
1
⇒ [0 + 0 − 1(0 − 3k)] = ±3
2
3k
⇒ = ±3
2
⇒ k = ±2
6.
(d) 0
Explanation:
0
1/5
7.
(c) 6
Explanation:
∣0 2 0 ∣
∣ ∣
λ 3 λ = - 16 then the sum of two values of λ is
∣ ∣
∣λ 5 6 ∣
∣0 2 0 ∣
∣ ∣
∣
λ 3 λ
∣
= -16 ⇒ - λ (12 - 0) + λ (2λ - 0) = -16
∣λ 5 6 ∣
8.
(d) infinitely many solutions
Explanation:
x + 2y = 5,
4x + 8y = 20
1 2 x 5
⇒ A=[ , X =[
] ,B=[
] ]
4 8 y 20
|A| = 8 -8 = 0
8 −2
adjA = [ ]
−4 1
8 −2 5 40 − 40 0
now (adj A)B= [ ][ ]= [ ]= [ ] ⇒ (adj A)B = 0
−4 1 20 −20 + 20 0
9.
(b) adj A
Explanation:
adj A
10.
−1
(b) (A T
)
Explanation:
−1
T
(A )
11.
(d) singular
Explanation:
If A is singular matrix then adjoint of A is also singular.This is true becaue , if A is a singular matrix, Then det(A) = 0 ,and
hence the adjoint will also be zero.
12.
33
(d) 2
Explanation:
When a given matrix is singular then the given matrix determinant is 0.
|A| = 0
Given,
2/5
1 k 3
⎛ ⎞
A= ⎜3 k −2 ⎟
⎝ ⎠
2 3 −4
|A| = 0
1(-4k + 6) -k(-12 + 4) + 3(9 - 2k) = 0
-4k + 6 + 12k - 4k + 27 - 6k = 0
-2k + 33 = 0
k= .33
13.
(b) 2
Explanation:
|A| = 2, |adj A| = |A|2 - 1 = |A| = 2
14.
(d) |A| = 22|B|
Explanation:
2 2 1 1
Let A = [ ] and B = [ ]
4 0 2 0
Now, |A| = 0 - 8 = -8
and |B| = 0 - 2 = -2
Observe that |A| = 4(-2) = 22 |B|
15.
(c) |A|6
Explanation:
If A is a non singular matrix of order 3, then |adj(A3)| = (|A3|)2 = (|AAA|)2 = (|A| |A| |A|)2 = (|A|3)2 = |A|6 .
Section B
∣ x 2 ∣ ∣ 6 2∣
16. we have, ∣ ∣ = ∣ ∣
∣ 18 x∣ ∣ 18 2∣
⇒ x2 – 36 = 36 - 36
⇒ x2 = 36
2
⇒ x + 1 = 36 + 1 = 37
Section C
17. We have |A| = = 1 (16 – 9) –3 (4 – 3) + 3 (3 – 4) = 1 ≠ 0
Now A11 = 7, A12 = –1, A13 = –1, A21 = –3, A22 = 1, A23 = 0, A31 = –3, A32 = 0, A33 = 1
7 −3 −3
⎡ ⎤
Therefore adjA = ⎢ −1 1 0⎥
⎣ ⎦
−1 0 1
1 3 3 7 −3 −3
⎡ ⎤⎡ ⎤
Now A(adjA) = ⎢ 1 4 3 ⎥ ⎢ −1 1 0⎥
⎣ ⎦⎣ ⎦
1 3 4 −1 0 1
7 − 3 − 3 −3 + 3 + 0 −3 + 0 + 3
⎡ ⎤
= ⎢7 − 4 − 3 −3 + 4 + 0 −3 + 0 + 3 ⎥
⎣ ⎦
7 − 3 − 4 −3 + 3 + 0 −3 + 0 + 4
3/5
1 0 0 1 0 0
⎡ ⎤ ⎡ ⎤
= ⎢0 1 0 ⎥ = (1) ⎢0 1 0 ⎥ = |A| ⋅ 1
⎣ ⎦ ⎣ ⎦
0 0 1 0 0 1
7 −3 −3 7 −3 −3
⎡ ⎤ ⎡ ⎤
Also A −1
=
1
adjA =
1
1
⎢ −1 1 0 ⎥ = ⎢ −1 1 0⎥ .
|A|
⎣ ⎦ ⎣ ⎦
−1 0 1 −1 0 1
A = ⎢3 4 −5 ⎥ , X = ⎢ y ⎥ and B = ⎢ −5 ⎥
⎣ ⎦ ⎣ ⎦ ⎣ ⎦
2 −1 3 z 12
∣3 −5 ∣
3
A12 = (−1) ∣ ∣ = −1(9 + 10) = −19
∣2 3 ∣
∣3 4 ∣
4
A13 = (−1) ∣ ∣ = 1(−3 − 8) = −11
∣2 −1 ∣
∣ −1 2∣
3
A21 = (−1) ∣ ∣ = −1(−3 + 2) = 1
∣ −1 3∣
∣1 2∣
4
A22 = (−1) ∣ ∣ = 1(3 − 4) = −1
∣2 3∣
∣1 −1 ∣
5
A23 = (−1) ∣ ∣ = −1(−1 + 2) = −1
∣2 −1 ∣
∣ −1 2 ∣
4
A31 = (−1) ∣ ∣ = 1(5 − 8) = −3
∣ 4 −5 ∣
∣1 2 ∣
5
A32 = (−1) ∣ ∣ = −1(−5 − 6) = 11
∣3 −5 ∣
∣1 −1 ∣
6
A33 = (−1) ∣ ∣ = 1(4 + 3) = 7
∣3 4 ∣
T
A11 A12 A13
⎡ ⎤
= ⎢ 1 −1 −1 ⎥
⎣ ⎦
−3 11 7
7 1 −3
⎡ ⎤
= ⎢ −19 −1 11 ⎥
⎣ ⎦
−11 −1 7
adj(A)
and A −1
=
|A|
7 1 −3
⎡ ⎤
= 1
4
⎢ −19 −1 11 ⎥
⎣ ⎦
−11 −1 7
4/5
Therefore, from Eq. (i), we get,
X = A-1B
x 7 1 −3 7
⎡ ⎤ ⎡ ⎤⎡ ⎤
1
⇒ ⎢y ⎥ = ⎢ −19 −1 11 ⎥ ⎢ −5 ⎥
4
⎣ ⎦ ⎣ ⎦⎣ ⎦
z −11 −1 7 12
x 49 − 5 − 36 8 2
⎡ ⎤ ⎡ ⎤ ⎡ ⎤ ⎡ ⎤
1 1
⇒ ⎢y ⎥ = ⎢ −133 + 5 + 132 ⎥ = ⎢4 ⎥ = ⎢1⎥
4 4
⎣ ⎦ ⎣ ⎦ ⎣ ⎦ ⎣ ⎦
z −77 + 5 + 84 12 3
5/5
Note: This service is not intended for secure transactions such as banking, social media, email, or purchasing. Use at your own risk. We assume no liability whatsoever for broken pages.
Alternative Proxies: